Homeowners' perception on mortgage financing: a case of bauchi metropolis Nigeria - Usman, Hamza (2016)
Mo1igage for financing house construction 1s essential for the attainment of homeownership in Nigeria. This research evaluated the perceptions of potential homeowners on mortgage financing in terms of attitude towards it, subjective norm, perceived behavioral control, religiosity and knowledge of mortgage financing and determined how these perceptions influence intention of using mortgage in financing house construction in Bauchi metropolis, Nigeria, using the Theory of Planned Behavior (TPB). Quantitative research approach using survey design was adopted. Data was collected using closed-ended questionnaires randomly distributed to a sample of 300 potential homeowners out of which 235 were considered valid for the analysis. Both descriptive and inferential statistical tools such as factor analysis and Partial Least Square-Structural Equation Modeling (PLS-SEM) were used to analyze the data using SPSS2 l and Sma1iPLS2 software. Overall, the research found that perceptions on mortgage financing was significant in predicting intention of using mortgage in financing housing construction because the model predict 77.6 percent (R2=0.776) of the variance. Thus, potential homeowner' perception on mortgage have significant effect on their intention of using mortgage in financing homeownership in Bauchi metropolis, Nigeria. Religiosity was found to be the most significant determinant (